STUDI MODAL SOSIAL PADA PENAMBANG EMAS TRADISONAL DI KELURAHAN MUARA BAKANON - Hazral Patma Jaya; Dimas Asto Aji An'Amta (Program Studi Sosiologi, FISIP ULM, 2023)
The background of this research is related to the existence of traditional gold mining activities carried out by the people of Muara Bakanon village on the Barito river, by looking at the Social Capital they use during mining activities. This study aims to find out how Social Capital is used by miners in carrying out traditional gold mining activities in Muara Bakanon Village. The method used in this research is descriptive-qualitative to provide a detailed description based on the facts found. The results of the findings in the field found that Social Capital in the form of values, norms, beliefs and social networks plays an important role in supporting relationships and relationships between miners during mining activities. If the Social Capital was not used during mining activities, perhaps this traditional gold mining would not survive until now and the relations and solidarity of the miners would not be formed in it.